(untitled) (Current Horticulture, 2024)
The role of exogenous supplementation of amino acids and casein hydrolysate in enhancing callogenesis from plumular explants of coconut (Cocos nucifera L.) was studied at ICAR-Central Plantation Crops Research Institute, Kasaragod, Kerala, during 2020-21. The combination of three amino acids, viz. glutamine, asparagine, proline, and organic additive casein hydrolysate were supplemented in three types of basal media (Eeuwen’s Y3, Murashige and Skoog (MS) and 1/2MS) containing 2, 4-D (16.5 mg/L), charcoal (0.1%) sucrose (3%) and agar (0.8%). A total of 19 treatments were formulated and tested for production of embryogenic colloid tissue. The explants in glutamine-supplemented medium generated better colloid tissue and showed positive effect on colloid tissue multiplication, compared to other combinations. Of three basal media, Y3 was better over 1/2MS and MS basal media. These results could be useful for improving the efficiency of in-vitro regeneration in coconut by somatic embryogenesis from plumular explants.